Antibiotic Combination Therapy: A Strategy to Overcome Bacterial Resistance to Aminoglycoside Antibiotics - Wang, Nuoyan; Luo, Jing; Deng, Fei; Huang, Yasi; Zhou, Hong (Frontiers in pharmacology, 2022)
After the first aminoglycoside antibiotic streptomycin being applied in clinical practice in the mid-1940s, aminoglycoside antibiotics (AGAs) are widely used to treat clinical bacterial infections and bacterial resistance to AGAs is increasing. The bacterial resistance to AGAs is owed to aminoglycoside modifying enzyme modification, active efflux pump gene overexpression and 16S rRNA ribosomal subunit methylation, leading to modification of AGAs’ structures and decreased concentration of drugs within bacteria. As AGAs’s side effects and bacterial resistance, the development of AGAs is time-consuming and difficult. Because bacterial resistance may occur in a short time after application in clinical practice, it was found that the antibacterial effect of the combination was not only better than that of AGAs alone but also reduce the dosage of antibiotics, thereby reducing the occurrence of side effects. This article reviews the clinical use of AGAs, the antibacterial mechanisms, the molecular mechanisms of bacterial resistance, and especially focuses a recent development of the combination of AGAs with other drugs to exert a synergistic antibacterial effect to provide a new strategy to overcome bacterial resistance to AGAs.